Sequence‐based mapping identifies a candidate transcription repressor underlying awn suppression at the B1 locus in wheat. Issue 1 (27th September 2019) - DeWitt, Noah; Guedira, Mohammed; Lauer, Edwin; Sarinelli, Martin; Tyagi, Priyanka; Fu, Daolin; Hao, QunQun; Murphy, J. Paul; Marshall, David; Akhunova, Alina; Jordan, Katherine; Akhunov, Eduard; et al.
Summary: Awns are stiff, hair‐like structures which grow from the lemmas of wheat ( Triticum aestivum ) and other grasses that contribute to photosynthesis and play a role in seed dispersal. Variation in awn length in domesticated wheat is controlled primarily by three major genes, most commonly the dominant awn suppressor Tipped1 ( B1 ). This study identifies a transcription repressor responsible for awn inhibition at the B1 locus. Association mapping was combined with analysis in biparental populations to delimit B1 to a distal region of 5AL colocalized with QTL for number of spikelets per spike, kernel weight, kernel length, and test weight. Fine‐mapping located B1 to a region containing only two predicted genes, including C2H2 zinc finger transcriptional repressor TraesCS5A02G542800 upregulated in developing spikes of awnless individuals. Deletions encompassing this candidate gene were present in awned mutants of an awnless wheat. Sequence polymorphisms in the B1 coding region were not observed in diverse wheat germplasm whereas a nearby polymorphism was highly predictive of awn suppression. Transcriptional repression by B1 is the major determinant of awn suppression in global wheat germplasm. It is associated with increased number of spikelets per spike and decreased kernel size.